Remimazolam combined with propofol for intraoperative wake-up testing in scoliosis correction surgery: a prospective, blind, randomized controlled trial - Luo, Jing; Chen, Da-Lin; Lv, Zong-Long; Zhong, Hui; Zhao, Yong-Hui; Li, Yu-Jin; Li, Xin-Nan; Chen, Jing-Ce; Shi, Wen-Bao; Bo, Yun; Lin, Rong-Qian; Yang, You-Zhi; et al. (Frontiers in Pharmacology, 2025)
PurposeRemimazolam is a fast-acting benzodiazepine used for anesthesia and sedation, notable for its quick onset and reversible effects. Its role in wake-up testing during spinal deformity surgery is uncertain. This study assessed the effectiveness and safety of combining remimazolam with propofol during wake-up tests in scoliosis correction surgery.MethodsIn this randomized trial, 54 scoliosis surgery patients were assigned to receive either propofol alone (Group P), propofol with dexmedetomidine (Group D), or propofol with remimazolam (Group R). Primary outcomes were wake-up time and quality; secondary outcomes included spinal monitoring, cerebral indices, hemodynamic stability, surgery duration, Visual Analog Scale and Behavioral Comfort Scale scores, satisfaction, and postoperative adverse events.ResultsMean wake-up times varied significantly across groups: 10.58 ± 1.60 min (Group P), 16.14 ± 2.64 min (Group D), and 6.69 ± 3.85 min (Group R) (p = 0.001). Post-hoc analysis revealed Group R had significantly shorter wake-up times than Group P (mean difference, 3.9 min; p = 0.0005) and Group D (mean difference, 9.4 min; p = 0.0001). Excellent wake-up quality was reported in 50% of Group P, 100% of Group D, and 94.4% of Group R (p = 0.0002). Group R also had a shorter mean operative duration (256.3 ± 74.4 min) compared to Group P (264.4 ± 60.4 min) and Group D (310.9 ± 57.9 min) (p = 0.03). Additionally, Group R showed significantly higher amnesia indices at multiple time points compared to Groups P and D (p < 0.05). Hemodynamic assessments revealed that Group D had significantly lower heart rates at T2, T3, and T4 than Groups P and R (p < 0.05). Group R also had a higher mean arterial pressure than Group P at T2 (p < 0.05). Surgeon satisfaction scores were significantly higher in Group R than in Groups P and D (p = 0.0001), and patient satisfaction scores in Group R were higher than in Group P (p = 0.0001). No significant differences were observed in other secondary outcomes (p > 0.05).ConclusionThe remimazolam-propofol combo for intraoperative wake-up testing in scoliosis correction surgery shows superior efficacy with quicker wake-up times, better wakefulness quality, and higher satisfaction, without affecting spinal neurophysiological monitoring. This suggests it as a promising sedative option for spinal deformity surgeries.Clinical Trial Registrationhttps://www.chictr.org.cn/bin/project/edit?pid=203900 as ChiCTR2300076802.